Aspectos técnicos e econômicos da dessalinização por nanofiltração de águas subterrâneas para abastecimento potável - Rojas, Fernando Cuenca (2017)
Dry periods are becoming a constant problem in many regions of the world, and it's no different in América do Sul. Countries like Brazil,Argentina, Paraguay, and Uruguay, share a huge indoor water reservoir, the Guarani Aquifer System (GAS). However, one should give importance to the quality of groundwater of the Guarani in some regions, as these can be brackish waters and the present presence of sulfates, fluorides, chlorides and total dissolved solids (TDS), disqualifying them for potability. The objective is to study the performance of nanofiltration membranes (NF), for desalination of water GAS technical and economic point of view in order to seek new alternatives of treatment for drinking water supply in populations at risk of shortages Water. Worked up with synthetic samples in order to meet the permeability and selectivity of NF membrane at various pressures and temperatures. The GAS water was collected in a subterranean well 834 (m) deep in Marcelino Ramos / RS, both samples as well the permeate 20 were characterized by physicochemical parameters, including heavy metals. With the sample of SAG independent variables were the two pressures (1 to 2 Mpa) and modulus volume reductionrate (VRR = 2, 3 and 4) to evaluate the dependent variable with the flow permeate and discards parameters: sulfate fluoride, electric conductivity, chloride, and SDT. We used a membrane KMS-2538-SR3D VYV Koch Membrane Systems with a unit area of 1.8 m² and was carried out in pilot experiments equipment over 70 minutes. The permeate fluxes were obtained in the best operating condition (pressure of 2 MPa and temperature of 30ºC) of 115.75 ± 0.77 (Lm-2h-1); sulfates rejections of 70%, 85% chlorides, fluorides and TDS 95% to 85%. Defined four scenarios analysis having two mixing models and the two operating pressures set. He designed a system with mixing to optimize the process with a recoveryof 91.6% of water, with a four-volume reduction rate (VRR = 4) and performing a technical assessment was chosen scenario 1. Assuming a population of 10,000 inhabitants for a small town in the Rio Grande do Sul, the necessary membranes to treat brackish water and pour this city is 314.16 m², for that requires 10 membranes with an area of 34.5 m² each membrane KMS-8038 SR3 VYV group. There was an evaluation of economic viability in the certainty condition of the four scenarios, considering the investment, operating and maintenance costs, construction costs of the desalination plant, among others, so scenario 1 was shown to be economically attractive, resulting in a final cost of treated water between 0.28 to 0.46 U$/m³ equivalent to 0.90 to 1,49 R$/m³. The nanofiltration PSM is a new alternative for the treatment of brackish groundwater and drinking water supplies, being attractive technically and economically to the field of desalination and new water sources in the future.